RANCANG BANGUN KURSI RODA UNTUK PENYANDANG DISABILITAS - Tri Agus Susanto; Uswatul Hasanah Mihdar (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Wheel chair is known as supportive tool required by disable persons in conducting their daily activities as well as to reduce the works of nurse or helper. The wheel chair could provide assistance for the disables in moving from one place to another effectively and efficiently. The research method was divided into three stages: (1) designing; (2) construction; and (3) technical testing. The designed wheel chair could handle loads up to 85 kg and the average time required to position the disable person to the wheel chair was only 15 seconds